2012
DOI: 10.1111/j.1600-0625.2012.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhancement of arsenic‐induced apoptosis via stimulating ROS‐dependent p53 protein ubiquitination in human HaCaT keratinocytes

Abstract: In this study, QUE, but not the structurally related chemical, rutin, enhanced the cytotoxicity of arsenic trioxide (As(+3)) against the viability of normal human HaCaT keratinocytes via induction of apoptosis. QUE enhancement of As(+3)-mediated apoptosis was accompanied by increased intracellular peroxide production according to a DCFH-DA analysis, and DNA ladders induced by QUE/As(+3) were inhibited by adding the antioxidative compound, N-acetyl cysteine (NAC). A loss of the mitochondrial membrane potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…Previously, we found that ATO, a drug clinically preferred for acute promyelocytic leukemia, decreases the stability of mutant p53 protein through a proteasome pathway, and blockage of proteasome pathway can alleviate the arsenic-induced mutant p53 degradation [32], [49]. In this study, we found that ATO induces expression of Pirh2 E3 ligase.…”
Section: Discussionmentioning
confidence: 55%
“…Previously, we found that ATO, a drug clinically preferred for acute promyelocytic leukemia, decreases the stability of mutant p53 protein through a proteasome pathway, and blockage of proteasome pathway can alleviate the arsenic-induced mutant p53 degradation [32], [49]. In this study, we found that ATO induces expression of Pirh2 E3 ligase.…”
Section: Discussionmentioning
confidence: 55%
“…Increased formation of malonaldehyde and protein carbonyls in frontal cortex and hippocampus of arsenic exposed rats indicate enhanced oxidative damage due to increased generation of reactive species and the finding is consistent with earlier reports (Bhadauria and Flora, 2007; Flora et al, 2009; Wang et al, 2012). As arsenic has a high affinity with thiols, it may affect free thiols and catalytic activity of proteins and enzymes containing thiols (Shen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS levels in HaCaT cells were determined by measuring the oxidative conversion of cell permeable 2 0 ,7 0 -dichlorofluorescein diacetate (H 2 DCFDA) to fluorescent dichlorofluorescein (DCF) (Shen et al, 2012). The fluorescence intensity of DCF in HaCaT cells is significantly increased with UVB irradiation, while the background ROS levels in HaCaT cells are low without irradiation.…”
Section: Measurement Of Intracellular Ros Levelmentioning
confidence: 99%